Mycoplasma Pneumonia in Young Children and Its Ways Of Treatment (Texas Journal of Medical Science, 2023)
This article provides information about pneumonia and some related diseases, such as mycoplasma pneumonia. The article explains how early children experience these diseases and how to treat them. Also, the article provides detailed information about the measures that children and parents need to follow in order to avoid this disease